Festival of colors - Sehgal, Kabir; Sehgal, Surishtha (Beach Lane Books, 2018)
Sibilings Chintoo and Mintoo collect flowers and press the petals into a fine powder as they prepare for Holi, the Indian springtime Festival of Colors. Includes author's note